2011
DOI: 10.1186/1477-7819-9-100
|View full text |Cite
|
Sign up to set email alerts
|

A male case of an undifferentiated carcinoma with osteoclast-like giant cells originating in an indeterminate mucin-producing cystic neoplasm of the pancreas. A case report and review of the literature

Abstract: We report a rare male case of an undifferentiated carcinoma with osteoclast-like giant cells originating in an indeterminate mucin-producing cystic neoplasm of the pancreas. A 59-year-old Japanese man with diabetes visited our hospital, complaining of fullness in the upper abdomen. A laboratory analysis revealed anemia (Hemoglobin; 9.7 g/dl) and elevated C-reactive protein (3.01 mg/dl). Carbohydrate antigen 19-9 was 274 U/ml and Carcinoembryonic antigen was 29.6 ng/ml. A computed tomography scan of the abdomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 15 publications
1
25
1
Order By: Relevance
“…Only three case reports described that the cysts in the tumors were lined by normal or atypical epithelial cells and formed a single cell layer. In addition, some authors have reported cases of ACP associated with mucinous cystic neoplasms[ 17 - 19 ], although the occurrence of histogenesis of ACP coincident with mucinous cystic neoplasm remains uncertain. These cases appear to display similar imaging findings to those of other forms of ACP with extensive cystic degeneration; however, in the present review, there were no reported cases of ACP coincident with mucinous cystic neoplasm in the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Only three case reports described that the cysts in the tumors were lined by normal or atypical epithelial cells and formed a single cell layer. In addition, some authors have reported cases of ACP associated with mucinous cystic neoplasms[ 17 - 19 ], although the occurrence of histogenesis of ACP coincident with mucinous cystic neoplasm remains uncertain. These cases appear to display similar imaging findings to those of other forms of ACP with extensive cystic degeneration; however, in the present review, there were no reported cases of ACP coincident with mucinous cystic neoplasm in the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Ours is the second case described in the english literature of an indeterminate mucin-producting cystic neoplasm containing an area of undifferentiated carcinoma with osteoclast-like giant cells. In a review that analyzed all cases of MCN associated with OGCC, 10 of 12 patients were alive at follow-up [ 6 ]. By contrast our report was remarkable for the rapid progression of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…In 1981, Posen described for the first time the association of a giant cell tumor of the osteoclastic type with a mucous secreting cystic pancreatic neoplasm and since then only 12 cases have been reported [ 5 , 6 ]. In a recent review Wada et al analyzing all the cases in the literature, reported a favourable prognosis for this particular tumor association [ 6 ]. We present the second case in the literature of a patient with an indeterminate mucin-producting cystic neoplasm containing a single area of undifferentiated carcinoma with osteoclast- like giant cells, characterized by a rapid disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…For example, some researchers have proposed that OGTP does not exhibit any sex-bias with respect to its development and that it has a relatively good prognosis as compared to other pancreatic tumors owing to the fact that OGTP typically only exhibits localized spreading, with metastasis to lymph nodes and distant sites being slow to develop and rarely reported [ 19 ]. In contrast, however, some researchers have reported OGTP to be more common in females [ 20 ] and to have a worse prognosis [ 21 , 22 ]. The site preferences for OGTP tumors similarly remains controversial.…”
Section: Introductionmentioning
confidence: 99%